Change in surface structure and inner microstructure of durum wheat pasta during the boiling process. (September 2021) - Ohmura, Masato; Matsumiya, Kentaro; Tatsuro, Maeda; Fujita, Akio; Hayashi, Yukako; Matsumura, Yasuki
Abstract: The aim of this study was to analyze changes in the surface structure and the inner microstructure of durum wheat pasta during the boiling process. Dried pasta was boiled for 1, 4, 7, or 10 min, and the structure of dried and boiled pasta was observed using polarizing light, laser, and fluorescence microscopy. The degree of gelatinization was measured by polarized light microscopy as well as the β-amylase-pullulanase method. The degree of gelatinization was shown to be larger when evaluated by polarized light microscopy. The surface roughness was evaluated by laser microscopy. The surface roughnesses of dried (non-boiled) pasta and boiled pasta showed different characteristics, and the calculation and analysis of parameters relating to surface roughness indicated that the surface of pasta becomes more uneven as boiling time increases. In principal component analysis of surface roughness, principal components 1 and 2 explained 71.7% of total variance. Principal component 1 mainly reflected the peak frequency and height, and principal component 2 mainly reflected the peak interval. We confirmed by fluorescence microscopy that starch granules began to swell from the outer periphery of the pasta during boiling, and the proportion of gluten network on the outer circumference structure clearly decreased. Highlights: We established a method for evaluating the surface roughness of pasta. As the boiling time increased, the proportion of gluten networks decreased in outer layer. The gelatinization degree by the loss of cross-polarized light was larger than that of β-amylase-pullulanase measurement.